2023
DOI: 10.1002/celc.202201118
|View full text |Cite
|
Sign up to set email alerts
|

A Thermodynamic Model for the Insertion Electrochemistry of Battery Cathodes

Abstract: The authors dedicate this paper to the memory of Alexander Milchev (1943Milchev ( -2022, a pioneer of nucleation/growth science and a researcher with highest human qualitiesThe transition to Ni-based battery cathodes enhances the energy density and reduces the cost of batteries. However, this comes at the expense of losing energy efficiency which could be a consequence of charge-discharge hysteresis. Here, a thermodynamic model is developed to understand the extent and origin of charge-discharge hysteresis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…This system is an example of a battery electrode that undergoes phase separation. 10 Fig. 3a (red curve) shows the CV of the Ni(OH) 2 /NiOOH electrode in the first and second cycles vs.…”
Section: Ni(oh) 2 /Niooh Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…This system is an example of a battery electrode that undergoes phase separation. 10 Fig. 3a (red curve) shows the CV of the Ni(OH) 2 /NiOOH electrode in the first and second cycles vs.…”
Section: Ni(oh) 2 /Niooh Systemmentioning
confidence: 99%
“…An example of a non-linear dynamic phenomenon is autocatalysis that has been used frequently to describe the dynamics of biochemical systems such as the evolution of life from simple molecules, 6,7 and recently, for studying the stability of reactive mixtures of relevance to batteries by Bazant et al 8,9 In a recent paper, we reported a thermodynamic treatment of phase separation in batteries. 10 Here, we study the consequences of this phase separation for solid-state electrochemical reactions using an autocatalytic model. This model reveals the autocatalytic nature of Ni(OH) 2 /NiOOH and Mn 2+ /MnO 2 reactions, as well as the origin of their asymmetric charge and discharge reactions, which may be a source of charge-discharge hysteresis, and hence, loss of energy efficiency in batteries.…”
mentioning
confidence: 99%
See 3 more Smart Citations